2003
DOI: 10.1007/s10048-003-0146-z
|View full text |Cite
|
Sign up to set email alerts
|

Association of dopamine D4 receptor (DRD4) exon III repeat polymorphism with temperament in 3-year-old infants

Abstract: The long forms of the dopamine D4 receptor (DRD4) exon III repeat polymorphism (L-DRD4) have been linked in some studies to the adult personality trait of novelty seeking (NS), as well as to infant personality traits related to interest and activity. The current investigation extends the results of our previous longitudinal study on 1- to 5-month-old neonates assessed by the Early and Revised Infancy Temperament Questionnaire (EITQ/RITQ), in which we found a significant correlation between the DRD4 polymorphis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 28 publications
2
21
0
Order By: Relevance
“…The results of our study are in accordance with the view that temperament is often under genetic control 18,19 and, therefore, independent of environmental influences. 19 In partial support of this view, recent research has identified various genetic polymorphisms related to specific temperament traits.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results of our study are in accordance with the view that temperament is often under genetic control 18,19 and, therefore, independent of environmental influences. 19 In partial support of this view, recent research has identified various genetic polymorphisms related to specific temperament traits.…”
Section: Discussionsupporting
confidence: 92%
“…19 In partial support of this view, recent research has identified various genetic polymorphisms related to specific temperament traits. [18][19][20][21] Progressive differentiation of the central nervous system correlates with the development of general movements in the early fetal period, whereas transient organization and further maturation of central nervous system is expressed as a behavioral pattern resembling goal-directed behavior in the late fetal period and transient behavioral pattern in the early neonatal period. 22 The results of our study suggest a need for further investigation of prenatal twins' activity in a larger sample.…”
Section: Discussionmentioning
confidence: 99%
“…Because certain temperament traits, such as behavioral inhibition and negative emotionality, are risk factors for psychopathology in later childhood (Biederman et al, 2001;Perkins et al, 1995) (Fendrich, Mackesy-Amiti, Johnson, Hubbell, & Wislar, 2005) their developmental determinates are of great interest. Temperament often is thought to be under genetic control (De Luca et al, 2001;De Luca et al, 2003;Goldsmith & Lemery, 2000; and therefore independent of environmental influences (Marshall et al). In partial support of this view, recent research has identified various genetic polymorphisms related to specific temperament traits (De Luca et al, 2000Dragan and Oniszczenko, 2005;Goldsmith and Lemery, 2000;Oniszczenko and Dragan, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…117,[160][161][162][163][164][165] As we first noted, 164,165 the study of temperament traits in children offers the opportunity to study gene effects at a time in development when environmental effects are conjectured to be minimal and genetic associations might be more robustly demonstrated.…”
mentioning
confidence: 99%